2017
DOI: 10.12669/pjms.331.11627
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of nutritional support by percutaneous endoscopic gastrostomy in critically ill patients: A self-control clinical trial

Abstract: Background & Objective:Percutaneous endoscopic gastrostomy (PEG) is a procedure to provide enteral nutrition for critically ill patients. It is commonly used in clinical practice; however, the widespread use of PEG is controversial. Our objective was to evaluate the therapeutic effect of nutritional support by PEG in these critically ill patients.Methods:A total of 64 critically ill patients including 41 males and 23 females (aged 23-84) were identified by the Acute Physiology and Chronic Health Evaluation (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…While it is reasonable to consider prophylactic GT placement prior to initiation of immunosuppressive medications, data from (PEG) tube placement in oncology patients showed no difference in complication rates regarding timing of placement . Use of GTs in other critically ill adult patient populations such as after cerebral hemorrhage or infarction has also been shown to be safe and effective with complication rates comparable to that of the general population . Overall complication rates in adults 30 days after conventional pull‐type PEG procedure range from 16% to 39% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is reasonable to consider prophylactic GT placement prior to initiation of immunosuppressive medications, data from (PEG) tube placement in oncology patients showed no difference in complication rates regarding timing of placement . Use of GTs in other critically ill adult patient populations such as after cerebral hemorrhage or infarction has also been shown to be safe and effective with complication rates comparable to that of the general population . Overall complication rates in adults 30 days after conventional pull‐type PEG procedure range from 16% to 39% .…”
Section: Discussionmentioning
confidence: 99%
“…30 Use of GTs in other critically ill adult patient populations such as after cerebral hemorrhage or infarction has also been shown to be safe and effective with complication rates comparable to that of the general population. 31 Overall complication rates in adults 30 days after conventional pull-type PEG procedure range from 16% to 39%. 32 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this is that there are difficulties with the measurement of height due to neuromuscular and genetic disorders present in the majority of children undergoing PEG. It has been reported that measurements such as UMAC and TST provide more accurate information in the growth monitoring of these patients 10,11 . We also used TST and UMAC measurements besides standard measurements in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…9 The In a study by Zhou et al, the triceps skinfold thickness and serum albumin level significantly increased at 4 th , 8 th and 12 th week after gastrostomy. 11 In another retrospective study where gastrostomy was done in head and neck cancer patients, the nutritional parameters like weight, BMI and serum albumin did not improve at 3, 6 and 12 months after gastrostomy. 12 In our present study also the BMI, serum albumin and the nutrition score did not improve significantly after the FG procedure.…”
Section: Stamm Described a Technique For Gastrostomy In 1894mentioning
confidence: 95%